Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.4137/bcbcr.s14920
|View full text |Cite
|
Sign up to set email alerts
|

Successful Remission of Hemolytic-Uremic Syndrome during the Third-line Weekly Gemcitabine for Metastatic Breast Cancer

Abstract: Sequential palliative chemotherapy for metastatic breast cancer incorporating weekly gemcitabine administered as three-weeks-on, one-week-off schedule is widely adopted throughout the East Asia region. Hemolytic-uremic syndrome (HUS) associated with weekly gemcitabine for a breast cancer patient is extremely rare. We report here a case of 43-year-old woman with metastatic breast cancer who received weekly gemcitabine as a third-line palliative chemotherapy for her disease. She developed HUS after a cumulative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…There is no fixed dose relationship but most studies have demonstrated that a cumulative dose in excess of 20,000 mg/m2 to be associated with the development of GiTMA. Hypertension, advanced stage of cancer, and prolonged gemcitabine treatment have been noted to be predisposing factors for the development of GiTMA [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is no fixed dose relationship but most studies have demonstrated that a cumulative dose in excess of 20,000 mg/m2 to be associated with the development of GiTMA. Hypertension, advanced stage of cancer, and prolonged gemcitabine treatment have been noted to be predisposing factors for the development of GiTMA [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, chemotherapy-induced MAHA has been reported as rare cases: Mitomycin C use has been implicated most frequently (George 2011 ; Bruntsch et al 1984 ), and gemcitabine use has been reported recently (Kok et al 2014 ). In cases of suspected chemotherapy involvement, some patients were reported to have recovered with symptomatic treatment such as discontinuation of the causative agent and blood transfusion (George 2011 ; Brain et al 1962 ; Bruntsch et al 1984 ).…”
Section: Discussion and Evaluationmentioning
confidence: 99%
“…Drug-induced MAHA and CR-MAHA are considered pathophysiologically distinct conditions. Chemotherapy is the only effective treatment for CR-MAHA, whereas plasma exchange is almost ineffective, with most patients dying within 2 weeks (1–10 days) (Pendse et al 2014 ; Lechner and Obermeier 2012 ; George 2011 ; Himmelmann and Schefer 2009 ; Lockhart 2001 ; Fontana et al 2001 ; Ataga and Graham 1999 ; Narita et al 1997 ; Nordstrom and Strang 1993 ; Bastecky et al 1992 ; Collins et al 1991 ; Canellos and Mark 1984 ; Kok et al 2014 ). In the study by Lechner et al that included other carcinomas, the median survival of patients receiving chemotherapy was 4 months and that of patients receiving either symptomatic treatment or no treatment was 0.5 months (Lechner and Obermeier 2012 ).…”
Section: Discussion and Evaluationmentioning
confidence: 99%